2016
DOI: 10.1016/j.parkreldis.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophic olivary degeneration: A clinico-radiologic study

Abstract: Introduction The frequency and causes of hypertrophic olivary degeneration (HOD) are unknown. We compared the clinical and radiological characteristics of unilateral HOD and bilateral HOD. Methods We performed a search of a radiologic report database for patients who were radiologically diagnosed as having HOD. This database includes the patients examined at the Mayo Clinic in Florida and Arizona. We used the search terms “hypertrophic olivary degeneration,” “HOD,” and “olivary” in the reports recorded from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 29 publications
(45 reference statements)
0
63
2
Order By: Relevance
“…Hypertrophic olivary degeneration is mostly bilateral, and half of bilateral cases may be implicated to primary neurodegenerative process 2. Our patient’s MRI revealed no abnormality involving the Guillain and Mollaret triangle.…”
Section: Descriptionmentioning
confidence: 54%
“…Hypertrophic olivary degeneration is mostly bilateral, and half of bilateral cases may be implicated to primary neurodegenerative process 2. Our patient’s MRI revealed no abnormality involving the Guillain and Mollaret triangle.…”
Section: Descriptionmentioning
confidence: 54%
“…HOD often remains asymptomatic and palatal tremor was seen in 39% of bilateral cases and in only 23% of the unilateral cases (Konno et al, 2016). HOD often remains asymptomatic and palatal tremor was seen in 39% of bilateral cases and in only 23% of the unilateral cases (Konno et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between palatal myoclonus and HOD remains controversial. HOD often remains asymptomatic and palatal tremor was seen in 39% of bilateral cases and in only 23% of the unilateral cases (Konno et al, 2016). It has been suggested that dysfunction of the ION rather than the hypertrophy is the cause of palatal tremor (Nishie et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis suggests a secondary degenerative process that may have been caused by venous hypertension and subsequent vasogenic edema as initial injury within the dentato‐rubro‐olivary pathway, formerly referred to as the Guillain–Mollaret triangle . Lesions involving this pathway, but sparing the olives, are known to cause denervation and degeneration of the ION and manifest as a tremor of branchial‐derived muscles . The underlying hypertrophic olivary degeneration (HOD) develops the most several weeks or months after denervation, which correlates with the delayed onset of the symptoms .…”
mentioning
confidence: 99%
“…1 Lesions involving this pathway, but sparing the olives, are known to cause denervation and degeneration of the ION and manifest as a tremor of branchial-derived muscles. [2][3][4] The underlying hypertrophic olivary degeneration (HOD) develops the most several weeks or months after denervation, which correlates with the delayed onset of the symptoms. 2,4 Moreover, contralateral atrophy of the cerebellar cortex and dentate nucleus may occur in association with HOD.…”
mentioning
confidence: 99%